Carbon footprint and the knowledge, attitudes and practices of students and staff at the secondary level on greenhouse gas emissions - Torres Ramos, Lidimed Kereine (2017)
This study aimed to determine the relationship between carbon footprint levels and the knowledge, attitudes, and practices of secondary School students and the staff of a Private Denominational School. The research was carried out in three parts: the calculation of the carbon footprint of the school, following the methodology of the Protocol of Greenhouse Gases; the measurement of the carbon footprint in the study population, through the calculator of emissions of Dragonfly Management in Climate Change and Communication, and the application of a test of knowledge, attitudes and practices. The results showed that the emissions per year in the educational institution were 25.36 tCO2e and the average emission of the study population was 2.18 tCO2e. Thecorrelation analysis showed that there is a negative correlation of -0.228 between the carbon footprint and the knowledge, attitudes, and practices of the population, that is when one increases, the other begins to decrease. In conclusion, according to the correlation analysis, there is a relationship between knowledge, attitudes and practices and the carbon footprint, however, it is a weak correlation, because the Person's index is below 0.5.